Regulation of the mec-3 gene by the C.elegans homeoproteins UNC-86 and MEC-3. - Xue, D (1992)
The mec-3 gene encodes a homeodomain protein with LIM repeats that is required for the specification of touch cell fate in Caenorhabditis elegans. Previous experiments suggested that mec-3 expression requires the product of the unc-86 gene, a POU-type homeoprotein, and mec-3 itself. We have analyzed the control of mec-3 expression by identifying potential cis regulatory elements in the mec-3 gene (by conservation in a related nematode and by DNase I footprinting using unc-86 and mec-3 proteins) and testing their importance by transforming C.elegans with mec-3lacZ fusions in which these sites have been mutagenized in vitro. Both unc-86 and mec-3 proteins bind specifically to the promoter of the mec-3 gene, suggesting that both proteins may be directly involved in the regulation of the mec-3 gene. In addition, the footprint pattern with mec-3 protein is altered in the presence of unc-86 protein. In vivo transformation experiments reveal that some of the binding regions of the two proteins are needed for general positive control and maintenance of mec-3 expression while others have no detectable, unique function. Interestingly, the unc-86 gene appears to be required not only to initiate mec-3 expression but also to maintain it.